Pengaruh Model Contextual Teaching and Learning Terhadap Hasil Belajar IPAS Siswa Kelas III SD Negeri 129/II Babeko - Ulia Ulia; Subhanadri Subhanadri; Tri Wera Agrita (Master Journal of Future Education, 2025)
This research is motivated by the Students’ difficulties in understanding the materials that explained by teacher and the lack of the learning models and materials related to students’ environment were the problems arised the background of the research. In addition, the other problems were the lack of the students’ involvement in teaching and learning (CTL) processes and the students’assumption that the science subject is only about memorization. Therefore, the students were not active in the learning processes. Eventually, these problems caused the low of the students’ learning outcomes. The purpose of this research was to investigate the effect of the Contextual Teaching and Learning (CTL) model on students’ learning outcomes on science of subject in second grade on SD Negeri 129/II Babeko regency. The type used in this study is an Quasi Experimental Design that is Non-equivalent Group Post-test Only Design type. In this research, there were experimental and control class. The experimental class was treated by using the Contextual Teaching and Learning (CTL) model, while the control class was not treated by Contextual Teaching and Learning (CTL) model. The population is a complete set of individual units whose characteristics want to be know. The population in this sttudy were all students of class III A and III B.The sampels of this research were 18 students of control class and 19 students of experimental class. The Measurements of the students’ learning outcomes were based on the research instruments in the form of multiple choice test. The results of the t-test calculation obtained by SPSS was ????ℎ???????????????????? > ???????????????????????? (2,273>1,689), at the significance 0,05 level, showed that the use of Contextual Teaching and Learning models effected the students’ learning outcomes. In addition the data obtained from the observations in this research was very good. The conclusion is that there is an increase in student learning outcomes between class III A who uses the ctl learning model and class III bstudents sho do not use the CTL learning model. From the results of the study, it is recommended that learning eith the CTL learning model can improve Student Learning outcomes, it should be used as an alternative in science learning activities, especially on the material of energy sources.